'A Completely Open Race': Anglo–Soviet Competition over German Military Science and Technology, 1944–1949. (April 2021) - Hall, Charlie
In the period immediately following the Second World War, during which Germany was occupied by the four victorious Allies, fierce competition erupted between them over the spoils of German military science and technology. Among this four-power squabbling, the British and Soviet authorities engaged in a particularly desperate struggle, especially over recruitment of expert German personnel, which they felt might give them the edge in any future conflict. This article explores the policies which arose from this struggle and shows that the first act of the Cold War arms race played out most vividly amongst the ruins of the Third Reich.